Prevalence of NRAS, PTEN and AKT1 gene mutations in the central nervous system metastases of non-small cell lung cancer - Nicoś, Marcin (Brain Tumor Pathol, 2017)
Somatic mutations in NRAS, PTEN and AKT1 genes are rarely (~1%) reported in primary NSCLC, but their role in carcinogenesis have been proven. Therefore, we assessed the frequency of them in 145 FFPE tissue samples from CNS metastases of NSCLC using the real-time PCR technique. We identified four (two NRAS and single AKT1 and PTEN) mutations in CNS metastases of NSCLC. All mutations were observed in current male smokers (4% out of the male group; 4/100 and 4.25% out of smokers; 4/94). Three mutations have been detected in patients with SqCC (10.3% out of SqCC patients; 3/29), and only one mutation in the NRAS gene—in a patient with adenocarcinoma (1.25% out of AC patients; 1/80). The examined genes were mutually exclusive in terms of molecular background in KRAS; EGFR; DDR2; PIK3CA; HER2 and MEK1 genes that were evaluated in our previous studies. The OS of the patients who harbored NRAS, AKT1 and PTEN mutations was 10.1, 12.1, 7.3 and 4 months, respectively (vs 13.5 months of the studied group). Our results suggest that the presence of NRAS, PTEN and AKT1 gene mutations may have an influence on the occurrence of CNS metastases in patients with SqCC.